Organizing inclusiveness in industrial and civil construction is a path to a barrier-free society - SHATROVA, Inna; DEMYDOVA, Olena (Ways to Improve Construction Efficiency, 2025)
In today’s world, where the principles of humanism and equal rights have become the cornerstone of societal development, the issue of inclusivity is gaining particular importance. Construction, as one of the fundamental sectors shaping the physical environment of our lives and activities, plays a key role in creating a barrier-free space. This is not merely a fashionable trend or a response to contemporary demands, but a vital necessity that ensures accessibility, comfort, and safety for all citizens, regardless of their physical or sensory abilities, age, or temporary limitations.Design effectively communicates essential information to users, regardless of environmental conditions or sensory capabilities. This includes the use of various forms of information presentation—visual, auditory, and tactile. For example, voice announcements in elevators combined with Braille buttons.Ukraine is actively working to align its regulatory framework with international standards in the field of barrier-free environments. Key documents include: The Constitution of Ukraine, which guarantees equality of rights and freedoms for all citizens; The Law of Ukraine “On the Fundamentals of Social Protection of Persons with Disabilities in Ukraine,” which defines the basic rights and guarantees for people with disabilities; The UN Convention on the Rights of Persons with Disabilities, ratified by Ukraine, which obliges member states to take all necessary measures to ensure access for persons with disabilities to the physical environment; State Building Norms (DBN) V.2.2-40:2018 “Inclusiveness. Basic Provisions,” a key document that establishes mandatory requirements for the design and construction of inclusive facilities. It details parameters for ramps, elevators, restrooms, evacuation routes, and other accessibility elements; DBN B.2.2-12:2019 “Planning and Development of Territories,” which also includes requirements for creating barrier-free spaces at the level of settlements.